Injuries Caused by Freshwater Stingrays in the Western Amazon: Folk Medicine and Beliefs - Da Silva, Greiciane Amorim; Poscai, Aline Nayara; Casas, André Luis da Silva (Ethnobiology Letters, 2020)
The envenomation caused by freshwater stingrays is one of the most frequent injuries related to aquatic animals in South America. Such injury is severe with skin necrosis as a probable result of the sting and subsequent intense pain. Here, we characterized the accidents caused by freshwater stingrays in Juruá Valley, Acre, Brazil, with reports of people who had suffered injuries. Data collection was performed in nearby communities in the Juruá River and its tributaries through a semi-structured questionnaire. Bathers and fishermen were the main group affected, and injuries were mainly in the lower limbs. The results were similar to those previously reported for other regions of Brazil, except for the treatment applied. Severe pain, edema, erythema, necrosis, and ulceration of the wound are some of the symptoms reported by the injured population. Most of the treatment is based on folk remedies, such as human urine, hot boiled egg, medicinal plants, and nonprescription drugs. In most cases, injuries usually occur in remote areas which favor the use of folk remedies, but the accidents are still neglected by the population itself because of the low lethality. Therefore, educational activities and prophylactic measures should be carried out with a standardization of first aid and late measures. In addition, the correct use of medicinal plants and folk remedies could be a strong ally to ensure a safe and affordable care for the population.